2013
DOI: 10.1080/13511610.2013.848163
|View full text |Cite
|
Sign up to set email alerts
|

Social innovation, an answer to contemporary societal challenges? Locating the concept in theory and practice

Abstract: Social innovation discourses see in social challenges opportunities to make societies more sustainable and cohesive through inclusive practices, coproduction and proactive grassroots initiatives. In this paper we are concerned first that the concept has been stretched in so many directions that it is at breaking point. We illustrate this by documenting the varied uses of social innovation in different academic and policy discourses. Second, we assume that, if social innovation is to be a useful concept for pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
221
0
36

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(258 citation statements)
references
References 51 publications
1
221
0
36
Order By: Relevance
“…We argue instead that this lack of rigour limits the potential of this concept, as a tool for both research and action. Based on our literature review, we observed that articles using the term SI often shift seamlessly between definitions of what SI is and what it should be (Borzaga and Bodini, 2014;Cajaiba-Santana, 2014;Grimm et al, 2013;Mieg and To¨ pfer, 2013;Novy and Leubolt, 2005;Pol and Ville, 2009). This use of the term occasionally leaves the reader unaware of what has been observed in practice and what the agents on the field, or the author, would like to have seen happen as a result of their own values.…”
Section: The Meaning(s) Of Social Innovationmentioning
confidence: 99%
See 2 more Smart Citations
“…We argue instead that this lack of rigour limits the potential of this concept, as a tool for both research and action. Based on our literature review, we observed that articles using the term SI often shift seamlessly between definitions of what SI is and what it should be (Borzaga and Bodini, 2014;Cajaiba-Santana, 2014;Grimm et al, 2013;Mieg and To¨ pfer, 2013;Novy and Leubolt, 2005;Pol and Ville, 2009). This use of the term occasionally leaves the reader unaware of what has been observed in practice and what the agents on the field, or the author, would like to have seen happen as a result of their own values.…”
Section: The Meaning(s) Of Social Innovationmentioning
confidence: 99%
“…In this context, SI refers to the social changes that had to happen in the structures of society to accommodate (or to trigger) new economic and political systems. It is therefore used as a generic concept that encapsulates, among other things, significant changes in government and governance, in the relationship between different social groups (or social classes) or in the role of religion in politics and society (Grimm et al, 2013;Jessop et al, 2013). This use of the term has nonetheless become less common, partly because the social sciences have in general moved away from structural analysis of big societal transformations in favour of more contextualised or micro-analysis of social phenomena (Scott, 2000).…”
Section: The Meaning(s) Of Social Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed by Eduardo Pol and Simon Ville (2009: 2), "[t]he term 'social innovation' has entered the discourse of social scientists with particular speed, but there is no consensus regarding its relevance or specific meaning in the social sciences and humanities." Some authors (e.g., Robert Grimm et al, 2013) have expressed concern that the concept has been stretched in so many directions, almost to the "breaking point". The intensification of discourse on the subject may be construed as a recognition of its topicality by some social scientists (e.g., Martin, 2006;Cajaiba-Santana, 2014), who have premised their discussion on the subject on the conviction that social innovation has a crucial role to play in efforts to achieve institutional change to better living conditions.…”
Section: Theoretical Background To Social Innovationmentioning
confidence: 99%
“…However, some innovations can give rise to wider change and create value for the society such as social innovation (Murray et al, 2010). Over the last decade, social innovation has gained the attention of academicians and policy-makers, and has been studied in different disciplines (Grimm, Fox, Baines, & Albertson, 2013;Rüede & Lurtz, 2012;Osburg & Schmidpeter, 2013). Murray et al (2010) define social innovations as "new ideas (products, services, and models) that simultaneously meet social needs and create new social relationships or collaborations" (p. 3).…”
Section: Defining Social Innovationmentioning
confidence: 99%